Extremely high thermal conductivity of carbon fiber/epoxy with synergistic effect of MXenes by freeze-drying. (June 2020) - Guo, Liangchao; Zhang, Zhenyu; Li, Maohua; Kang, Ruiyang; Chen, Yapeng; Song, Guichen; Han, Su-Ting; Lin, Cheng-Te; Jiang, Nan; Yu, Jinhong
Abstract: As the power density of the electronics is on increasing, improving the heat dissipation performance of electronic packaging materials will play a positive role in promoting the performance of modern electronics. In this work, the three-dimensional carbon fiber (CF)-MXenes foam, in which the vertically aligned CF constructed the heat transport paths, were prepared by simple freeze-drying method. As a result, the thermal conductivity (TC) of CF-M/epoxy composites was improved to an ultra-high level (9.68 W/mK) at 30.2 wt% hybrid fillers, increasing by 4509% enhancement compared with that of neat epoxy. In addition, the thermal properties of composites, such as glass transition temperature (Tg), coefficient of thermal expansion (CTE) were investigated. All the results indicated that the CF-MXenes/epoxy composite was supposed to be a promising heat dissipation material and will be used in the field of electronic packaging. Highlights: The vertical aligned carbon fiber-MXenes foams construct thermal transport channels in polymer composites. The thermal conductivity of CF-M/epoxy composite with 30.2% hybrid fillers was 9.68 W/mK. The CF-M/epoxy composite retains the low coefficient of thermal expansion.